Characteristics of Riobamba's household solid waste generation and the benefits of source separation (Journal of Namibian Studies : History Politics Culture, 2023)
The generation of urban waste represents a problem for cities, so quantifying and analyzing its generation is fundamental for municipal planning. To obtain these data, a study was conducted in Riobamba, forty households were selected, and data were collected, phase I determined the composition of the waste based on the quartering methodology, in phase II a pilot source sepa-ration program was implemented and quantified, with the data obtained estimates were made according to different percentages of recovery of materials compared to the extension of the useful life of the landfill. The result showed that the generation rate per capita was 0.71 kg/person/day, translated into about 200 tons of waste generated per day in Riobamba city. In terms of compo-sition, the fraction of organic waste constitutes the largest proportion in the two phases with percentages of 60% and 73%, recyclables 20% and 12% and disposable 20% and 15%, which indicates that in the phase of separation at the source, the families created more awareness about the gen-eration of waste, so it is important to implement management practices to reduce the waste volume to a final disposal which will contribute to extend the useful landfill life up to 27 years.